THEORETICAL BASIS FOR THE DETERMINATION OF RATIONAL PARAMETERS OF COMPLEX MECHANICAL SYSTEMS - Myamlin, S. V.; Prykhodko, V. I. (Science and Transport Progress, 2007)
The mathematical description of choosing the parameters of mechanical systems in general form and with eking account of the features of rail vehicles is presented. The examples of solution of vector optimization problems according to several indices are considered.